Zdroje informací studentů pražských gymnázií o občanech bývalé Jugoslávie - Procházka, Tomáš (Lidé města, 2000)
The paper focuses on the question of contacts and sources of information about the citizens of the former Yugoslavia as ascertained among the students of three Prague secondary schools (born in 1976-1978). The survey was conducted in 1995 by means of a questionnaire method and non-standardized interviews. The role of the media as a source of information about the citizens of the former Yugoslavia is indispensable. The respondents (82.93 %) clearly prefer television. The rest of the media is placed by the respondents under the limit of 50 %. This involves the press, literature and radio. Direct contact and information mediated by another person are generally not considered as crucial by the respondents. This also relates to the school. Despite this, 69 % of respondents said that their experience with a citizen of the former Yugoslavia materialized through direct contact. In direct contact there was also a focus on distinguishing ethnic groups of the former Yugoslavia. If the respondents named them, there was a dominance of three nations of the former Yugoslavia-Croatians, Serbs and Moslems.